Model Complexity as Determining Factor for In Vitro Nanosafety Studies: Effects of Silver and Titanium Dioxide Nanomaterials in Intestinal Models. Issue 15 (18th January 2021) - Kämpfer, Angela A. M.; Busch, Mathias; Büttner, Veronika; Bredeck, Gerrit; Stahlmecke, Burkhard; Hellack, Bryan; Masson, Isabelle; Sofranko, Adriana; Albrecht, Catrin; Schins, Roel P. F.
Abstract: With the rising interest in the effects of orally ingested engineered nanomaterials (ENMs), much effort is undertaken to develop and advance intestinal in vitro models. The cytotoxic, proinflammatory, and DNA damaging properties of polyvinylpyrrolidone‐capped silver (Ag‐PVP) and titanium dioxide (TiO2, P25) ENM in four in vitro models of increasing complexity—from proliferating Caco‐2 and HT29‐MTX‐E12 monocultures to long‐term transwell triple cultures including THP‐1 macrophages to reproduce the human intestine in healthy versus inflamed‐like state—are studied. Results are compared against in vivo effects of the same ENM through intestinal tissue analysis from 28‐day oral exposure studies in mice. Adverse responses are only observed in monocultures and suggest toxic potential for both ENM, typically showing stronger effects for Ag‐PVP than for TiO2 . By contrast, no adverse effects are observed in either the transwell cultures or the analyzed murine tissues. The data provide further support that monoculture models represent a cost and time efficient tool for early‐phase hazard assessment. However, the observed similarities in morphology and ENM effects in murine intestinal tissue and the in vitro triple culture model suggest that advanced multifacetted research questions concerning oral ENM exposure are more adequately addressed by the more complex and time intensive models. Abstract : In intestinal in vitro research, the choice of model impacts the outcomes. Strongest effects of silver and titanium dioxide particles are observed in proliferating monocultures. Negligible responses are quantified in complex multicell systems in healthy or inflamed state, which align with the outcomes of feeding studies in mice using the same nanomaterials.